GAYA BELAJAR MAHASISWA DI ERA CYBER PEDAGOGY MELALUI PENDEKATAN SELF ORGANIZIED LEARNING ENVIRONMENT - Sri Yunita; Jamaludin Jamaludin (PREDIKSI (PROFESI PENDIDIKAN INDONESIA), 2022)
This study aims to describe student learning styles in learning civic education through self-organized learning environment in cyber pedagogy space. In the industrial era 4.0, all access is focused on internet-based digital readiness and establishment, starting from the Internet of Things IoT to focusing on everything relying on the internet of everything IoE. An unlimited connection space in searching for information and knowledge, especially on student learning needs independently, is created through a self-organized learning environment (SOLE) starting from the user, data/information/knowledge, process and implementation of learning activities. The orientation of this research looks at the learning process and learning outcomes of Civics learning which can be seen from the student's learning style according to the honey and momfurd theory through the SOLE method of learning approach. Data were obtained through observation, interviews, FGD (focus group discussion) and documentation studies. The data were analyzed using data reduction analysis techniques, data presentation and conclusion drawing. The results and conclusions show that in welcoming the profile of future Civics teacher candidates in the cyber pedagogy space requires readiness and establishment as an internet-based digital user, Civics content has experienced significant development due to the influence of the era of fast-paced change, access to information and communication goes hand in hand and is renewable in sharing issues. -Citizenship issues on the scale of ethnicity, nationality and cosmopolitan require student learning styles that are reflective, theoretical, activist, and pragmatic.